The high burden of anxiety and depression among cancer patients undergoing the transition to palliative care (Revista Internacional de apoyo a la inclusión, logopedia, sociedad y multiculturalidad, 2018)
The objective was to evaluate the indicators of pain, anxiety and depression through early screening in patients admitted to a palliative care oncology service. This was a cross-sectional with outpatients. We used the Hospital Anxiety Depression Scale; Visual Analog Scale of Pain and sociodemographic information from the medical record. 70 (32.6%) patients had some degree of pain. And moderate or excruciating 10 (5%), pain. It was found that 80 (37.2%) patients had anxiety and 84 (39.1%) depression. And 48 (22.4%) and 60 (27.9%) of them were within the moderate or severe levels for anxiety and depression respectively. Early tracking of pain, anxiety and depression is recommended to favor immediate patients admitted to hospice care practice.